2014
DOI: 10.1002/ps.3768
|View full text |Cite
|
Sign up to set email alerts
|

Differential mechanisms of action of the novelγ-aminobutyric acid receptor antagonist ectoparasiticides fluralaner (A1443) and fipronil

Abstract: The findings indicate that rdl-type fipronil-resistant pests do not show cross-resistance to fluralaner owing to the differential actions of fluralaner and fipronil on the GABAR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 17 publications
2
49
0
Order By: Relevance
“…aegypti adults (1.3 ng/mg at 24 h). Additionally, Asahi et al [24] showed that fluralaner had similar potent toxicity on fipronil-resistant and susceptible strains of Laodelphax striatellus Fallén, whereas fipronil showed a resistance ratio of about 1700. These findings are in agreement with results of both feeding and glass contact assays on dieldrin-resistant and susceptible strains of D. melanogaster reported here, where fluralaner showed similar activity at all recorded time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti adults (1.3 ng/mg at 24 h). Additionally, Asahi et al [24] showed that fluralaner had similar potent toxicity on fipronil-resistant and susceptible strains of Laodelphax striatellus Fallén, whereas fipronil showed a resistance ratio of about 1700. These findings are in agreement with results of both feeding and glass contact assays on dieldrin-resistant and susceptible strains of D. melanogaster reported here, where fluralaner showed similar activity at all recorded time points.…”
Section: Discussionmentioning
confidence: 99%
“…In two-electrode voltage clamp (TEVC) recordings of oocytes expressing M. domestica RDL receptors, fluralaner had similar IC 50 values of 2.8 nM on rdl -type receptors with A299S mutation and 5.3 nM on wild-type receptors [10]. Fluralaner also had an IC 50 value of 12 nM on fipronil-resistant RDL receptors from a plant-feeding mite, Tetranychus urticae Koch, in TEVC experiments, whereas 30 µM of fipronil only blocked 27% of GABA-induced current [24]. In the present study, fluralaner was tested on native D. melanogaster GABA receptors, in situ, instead of heterologously expressed RDL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of evidence establish that isoxazolines [57][58][59][60][61][62][63][64][65][66] and meta-diamides (including mDA-7 [24,67] and BPB-1 [68]) are NCAs but at a different high affinity site(s) than those for compounds acting at the NCA-IA, NCA-IB and AVE targets ( …”
Section: Nca Actionmentioning
confidence: 99%
“…A 2012 compilation considering the chronology and numbers for introduction of the current insecticides gave the GABA-R targeting compounds as only 1.7% of the total with half of them introduced by 1955 [81]. Newly introduced GABAergic insecticides are flu and afoxolaner used for flea and tick control on cats and dogs [58,[62][63][64][65]. There are also important crop pests highly sensitive to NCA-IIs [24,60,82] indicating possible expanded use on optimization.…”
Section: Prospectsmentioning
confidence: 99%
“…Pyrethroids like deltamethrin (DEL) kill insects by acting on sodium channels [6], and neonicotinoids like acetamiprid (ACE) act as agonists of the nicotinic acetylcholine receptors [7,8], whereas organophosphates like chlorpyrifos (CHL) inhibit the action of the acetylcholinesterase, resulting in increased acetylcholine concentrations at the synapses [9,10]. More recent compounds like the phenylpyrazol fipronil (FIP) act as agonists of the insect RDL GABA receptors [11,12]. In all cases, insecticides are neurotoxic because they disrupt neurotransmission and alter insect behavior or survival [13].…”
Section: Introductionmentioning
confidence: 99%